Currency mismatch, uncertainty and debt maturity structure - Matthieu Bussière; Marcel Fratzscher; Winfried Koeniger (European Central Bank (ECB), 2004)
The academic literature has so far little to say about the underlying causes of the large structural asset and liability imbalances of emerging markets that frequently contributed to financial crises. The aim of the paper is to contribute to filling this gap by proposing a theoretical model that links currency and maturity mismatches with real volatility in the economy. We show that if (i) a significant share of the debt is denominated in foreign currency-creating a currency mismatch- and (ii) borrowing is constrained by solvency, then currency mismatch can create and exacerbate a maturity mismatch. An important feature of the model is that higher economic or political uncertainty tightens solvency constraints and tilts the debt profile towards short term debt, thereby increasing the volatility of output. Taking the model implications to the data, we find empirical support for the model's predictions using data for 28 emerging market economies.
Keywords: F34; F36; 330; currency mismatch; debt; emerging markets; Maturity mismatch; uncertainty